Oral Drotaverine and Aceclofenac Combination versus Aceclofenac alone for Postoperative Pain Relief: A Prospective Randomized Clinical Trial - KM, Vinod; D, Ashish (Indian Journal of Pharmacy Practice)
Objective:To compare the efficacy of Drotaverine- Aceclofenac combination with Aceclofenac alone in treatment of postoperative spasm and pain. Methods: In a prospective Randomized Clinical Trial, patients undergoing laparoscopic surgeries not involving bowel resections were enrolled. Group 1 received 80 mg Drotaverine and 100 mg Aceclofenac combination while Group 2 received 100 mg Aceclofenac alone. Pain was assessed by a 10-point visual analog scale on day 1, 3 and 5 after surgery. Results: We recruited 70 cases in each group. Group 1 showed statistically significant reduction in pain scores at day 1, 3 and 5, postoperatively. The scores for Global assessment and general evaluation by doctor were statistically higher in group 1. Group 1 also experienced relatively less adverse events. Conclusion: Drotaverine with Aceclofenac combination is more effective than Aceclofenac alone in treatment of postoperative pain after laparoscopic procedures which do not involve bowel resections or extensive bowel handling.
Keywords: Drotaverine; Aceclofenac; laparoscopic surgery; pain relief